Volga Bulgaria and the East during the 11th – 12th Centuries (Based on Materials of the Excavations at Ostolopovo Settlement in the Mouth of the Shentala River of Alekseevskii District of the Republic of Tatarstan) - K.A. Rudenko (Ученые записки Казанского университета: Серия Гуманитарные науки)
The paper considers the unique materials of archaeological research on a Bulgarian settlement near the village of Rechnoe in Alekseevskii district of Tatarstan (Ostolopovo Settlement). These are fragments of glazed ceramics, glass ornaments, ornamental stones, fragments of artistic metal bowls, and coins. All these items were carried to the settlement from the eastern countries (Iran, Central Asia, Egypt, and Syria). The findings were precisely dated, mostly within the limits of the 11th century. Such artefacts as a piece of the Egyptian perfume bottle dated to the 11th century, a set of iron plates from an amour of the same time are of particular interest. They are similar to other findings from Central Asia, being either very rare in the Bulgarian antiquities or found for the first time. These artefacts were brought to the settlement from Bilär, the great medieval city. Most artefacts have been dated stratigraphically. In the archeology of Bulgarian settlements, such cases are very uncommon. The artefacts from occasional findings made in the destroyed occupation layer of this settlement have been also studied. These are iron balance weights, glass beads, as well as lazurite and agate ornaments. The small cones made of lead and some pieces of this metal are unusual. They were used in jewelry making. Furthermore, they could have replaced coins. There was only one silver coin found at Ostolopovo Settlement during the excavation works. It was minted in the end of the 10th century during the rule of the Buyid dynasty and has an aperture for hanging. Therefore, it was used as a necklace detail. Thus, it is for the first time when the precisely dated archaeological material has been obtained, thereby proving a large import of rare items from the eastern countries into rural Bulgarian settlements during the 11th – 12th centuries.